Progressividade tributária do IPTU e sua relação de proteção do meio ambiente urbano em Morrinhos/GO - (:unkn) unknown (Universidade Estadual de Goiás, 2021)
The present dissertation aims to analyze the tax progressivity of the IPTU and its relation of protection of the urban environment in Morrinhos/GO. For this, 130 (one hundred and thirty) taxpayer extracts were collected, randomly and automatically by the electronic management system at the city hall of Morrinhos/GO, in order to affirm that the IPTU rates were not increased or bet on their extra-fiscal character, between the years 2015 and 2019 in the aforementioned municipality. Through bibliographic research, the historical origin of the IPTU was investigated, in parallel with the phases of development of the national tax system, as well as the general legal principles applicable to the tax, as well as its relation of preservation of the ecological environment. In addition, the taxable event of the IPTU and its hypothesis of tax incidence were addressed, as well as the origin, concept and legal nature of tax progressivity. When seeking greater familiarity with the object, the annual tax revenue and certain methods of progression adopted in four Brazilian capitals were examined, as well as the general guidelines of urban policy regarding the extrafiscal progressive IPTU and the subsumption of the theory of tax progressivity, in regarding the Tax Code of Morrinhos/GO. After analyzing the extracts and preparing the calculations that prove the representativeness of the minimum sample, the neighborhoods that most appear in the sample and those that are least repeated, as well as the taxpayers that have more than one urban property in Morrinhos/GO, were illustrated by means of a graph. In addition, of course, the relationship of its urban properties with the neighborhoods and regions of the municipality. The regions where the main real estate investments are concentrated in Morrinhos/GO were also highlighted, fragmenting urban properties into residences, commercial establishments and lots. In the end, the stated hypothesis that there was no variation in the IPTU rates within the aforementioned period of time was confirmed. Thus, it was concluded that such a tax was not used to protect the urban environment in Morrinhos/GO, between the years 2015 and 2019, through its extra-fiscal function. In other words, the extrafiscal progressiveness of the IPTU is not impacting on issues related to the urban environment in Morrinhos/GO. The non-interference is justified by the lack of legal provision that attributes to the fiscal operators of the City Hall the requirement of professional training in Law. For, without technical knowledge of legal hermeneutics, they do not see the possibility of applying tax progressivity in favor of the sustainable ecological system. However, there is also a failure of the main responsible for public administration: mayor and secretaries, especially for administration and finance. When these agents in the exercise of their mandate, position, employment or public function fail to apply the progressive tax rates, even if expressly determined by law, it constitutes an act of administrative improbity that harms the public purse. Finally, we suggest, by increasing the rates of the IPTU, an expansion of the tax collection to revert public health, with the purpose of solving the environmental problem of the municipality of Morrinhos/GO, pertinent to the abandonment of animals and their uncontrolled reproduction.
Keywords: Progressividade tributária do IPTU; Imposto Predial e Territorial Urbano (IPTU); Proteção ambiental; Abandono de animais; Reprodução descontrolada; Progressivity of the IPTU; Protection environmental.; CIENCIAS SOCIAIS APLICADAS::DIREITO